2014
DOI: 10.7322/jhgd.72041
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic global parameters correlation with heart rate variability in obese children

Abstract: The aim of the study is to analyze heart rate dynamics in obese children by measures of HRV. HRV is a simple and non-invasive measure of autonomic impulses. 94 children of mixed gender aged eight to twelve years were divided into two equal groups based on body mass index: obese and normal weight range. HRV was monitored in the dorsal decubitus position for 20 minutes. After tests of normality, Kruskal Wallis was applied for the statistical analysis, with the level of significance set at (p < 0.05). Regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 41 publications
2
38
0
4
Order By: Relevance
“…sMTM is the value of the area between the MTM spectrum and the baseline. There has been speculation 14,15 that if spectral entropy and sDFA previously applied to Welch power spectra were applied to multi-taper spectra which are adaptive and more sensitive; results may have greater chaotic parametric response.…”
Section: Introductionmentioning
confidence: 99%
“…sMTM is the value of the area between the MTM spectrum and the baseline. There has been speculation 14,15 that if spectral entropy and sDFA previously applied to Welch power spectra were applied to multi-taper spectra which are adaptive and more sensitive; results may have greater chaotic parametric response.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a major public health problem [11]. Consequences include arterial hypertension, atherosclerosis, diabetes, sleep apnea and depression; amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…CFP1 is expected to be the case as it was so in the previous studies by Souza, et al [12] and Vanderlei, et al [13]. Nevertheless, CFP3 with the sDFA parameter absent is more significant.…”
Section: Discussionmentioning
confidence: 67%
“…It is suggested that the length of the time-series be doubled to 1000 RR intervals. This was the case for previous studies by Souza, et al [12] and Vanderlei, et al [13]. Only half this recommended length of data was practiced here.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation